Social Reward Dependence and Brain White Matter Microstructure - Bjørnebekk, Astrid (Cereb Cortex, 2012)
People show consistent differences in their cognitive and emotional responses to environmental cues, manifesting, for example, as variability in social reward processing and novelty-seeking behavior. However, the neurobiological foundation of human temperament and personality is poorly understood. A likely hypothesis is that personality traits rely on the integrity and function of distributed neurocircuitry. In this diffusion tensor imaging (DTI) study, this hypothesis was tested by examining the associations between reward dependence (RD) and novelty seeking (NS), as measured by Cloninger’s Temperament and Character Inventory, and fractional anisotropy (FA) and mean diffusivity (MD) as DTI-derived indices of white matter (WM) microstructure across the brain. The results supported the hypothesis. RD was associated with WM architecture coherence as indicated by a negative correlation between RD and FA in frontally distributed areas including pathways connecting important constituents of reward-related neurocircuitry. The associations between RD and FA could not be explained by age, sex, alcohol consumption, or trait anxiety. In contrast, no effects were observed for NS. These findings support the theory that WM fiber tract properties modulate individual differences in social reward processing.